Gender Trouble in Social Psychology: How Can Butler’s Work Inform Experimental Social Psychologists’ Conceptualization of Gender? - Morgenroth, Thekla; Ryan, Michelle K. (Frontiers in Psychology, 2018)
A quarter of a century ago, philosopher Judith Butler (1990) called upon society to create “gender trouble” by disrupting the binary view of sex, gender, and sexuality. She argued that gender, rather than being an essential quality following from biological sex, or an inherent identity, is an act which grows out of, reinforces, and is reinforced by, societal norms and creates the illusion of binary sex. Despite the fact that Butler’s philosophical approach to understanding gender has many resonances with a large body of gender research being conducted by social psychologists, little theorizing and research within experimental social psychology has drawn directly on Butler’s ideas. In this paper, we will discuss how Butler’s ideas can add to experimental social psychologists’ understanding of gender. We describe the Butler’s ideas from Gender Trouble and discuss the ways in which they fit with current conceptualizations of gender in experimental social psychology. We then propose a series of new research questions that arise from this integration of Butler’s work and the social psychological literature. Finally, we suggest a number of concrete ways in which experimental social psychologists can incorporate notions of gender performativity and gender trouble into the ways in which they research gender.